Recent advances with liposomes as drug carriers for treatment of neurodegenerative diseases - Seo, Min-Wook; Park, Tae-Eun (Biomedical engineering letters, 2021)
A major challenge in treating neurogenerative diseases is delivering drugs across the blood–brain barrier (BBB). In this review, we summarized the development of liposome-based drug delivery system with enhanced BBB penetration for efficient brain drug delivery. We focused on the liposome-based therapeutics targeting Alzheimer's disease and Parkinson's disease because they are most common types of adult chronic neurodegenerative disorders. A variety of liposome with surface modification of BBB-targeting ligands have been created to cross the BBB via transcytosis to the therapeutic efficacy of Alzheimer’s disease and Parkinson’s disease drugs. Recent advances in liposome are providing alternatives to overcome BBB for more efficient therapeutic strategy. To improve the BBB penetration of liposomes, we need to completely understand the pathophysiological changes at the BBB.